Awake tracheal intubation with the ProVu™ video stylet: a case series - Harrison, S‐L. (John Wiley and Sons Inc., 2021)

(untitled) (Anaesth Rep)
Management of the difficult airway is integral to peri‐operative practice. The development of devices to simplify airway handling are changing our approach to tracheal intubation. We report a case series of three patients who underwent awake tracheal intubation with the ProVu™ video stylet (Flexicare Medical Ltd, Mountain Ash, UK). All three patients had predicted difficult airways, including: limited mouth opening secondary to radiotherapy; previous exenteration, hemi‐maxillectomy and scapular free flap formation; and cervical fixation. Awake tracheal intubation was performed successfully in all three cases, with no complications reported. This is the first reported case series of the ProVu™ video stylet as an awake tracheal intubation device. The benefits and limitations of this video stylet are discussed.